Phacomatosis pigmentokeratotica associated with unilateral toe walking due to short achilles tendon - SALMAN, ANDAÇ; YÜCELTEN, AYŞE DENİZ; ÜNVER, OLCAY (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2020)
Phacomatosis pigmentokeratotica (PPK) is characterized by the co-occurrence of speckled lentiginous nevus (nevus spilus) and an organoid nevus with or without extracutaneous involvement. The extracutaneous manifestations may vary widely with musculoskeletal, neurologic, ocular, and vascular findings. The PPK is also associated with an increased risk of cutaneous or extracutaneous tumors. Therefore, the patients with PPK should be followed up regularly for possible malignant transformation. Here, we report a 5-year-old boy with PPK associated with toe walking due to short Achilles tendon, which was not previously reported, to our knowledge.
Keywords: Genetic diseases; mechanisms; genodermatoses; neoplasms-benign